Combination of cyclophosphamide and interferon-β halts progression in patients with rapidly transitional multiple sclerosis. Issue 3 (1st September 2001) - Patti, F; Cataldi, M L; Nicoletti, F; Reggio, E; Nicoletti, A; Reggio, A
Abstract : The effects of combined treatment with cyclophosphamide (CTX) and interferon-β (IFN-β) are described in selected patients with "rapidly transitional" multiple sclerosis. This form of multiple sclerosis is extremely active with very frequent and severe attacks which produce a dramatic increase on the expanded disability status scale (EDSS). Ten patients with rapidly transitional multiple sclerosis were previously treated with interferon-β, but none benefited by this treatment. Monthly treatment with intravenous CTX, from 500 mg/m 2 to 1500 mg/m 2 to obtain a chronic lymphocytopenia (600/mm 3 to 900/mm 3 ) produced a marked and significant reduction in the number of relapses (p<0.0001), disability previously accumulated (p<0.0001), and a reduction of T2 MRI burden of lesion. This particular group of patients benefited by combining cyclophosphamide and IFN-β. The possibility is considered of carrying out further studies to test the efficacy of the association between the two drugs for patients who are not responsive to IFN-β or other active disease modifying therapies.